General psychopathology and impulsivity as the pre-treatment predictors of medical nutrition therapy outcome in the overweight and obese women - Tepšić-Ostojić Vesna; Ristić-Medić Danijela; Mraović Tatjana; Bukumirić Zoran; Vasiljević Nađa; Latas Milan (Vojnosanitetski Pregled, 2019)
Background/Aim. Obesity is the chronic disease and health threatening condition. The number of obese people in the world has taken epidemic conditions. Medical nutritional therapy is the first choice in the treatment of obesity, but it is also accompanied with a great percentage of attrition and a significant weight regain. The aim of our study was to evaluate if psychiatric and specific psychological factors (impulsivity) could be the predictors of successful weight loss. Methods. A study sample consisted of 84 consecutive overweight/obesity women, 20 to 40 years old, who were willing to adhere to the medical nutrition therapy after the initial anthropometric measurements were performed. All participants received a personalized nutritional counseling and a daily diet treatment with 20% caloric restriction from estimated daily energy requirement. At the beginning of the study, the 90-item Symptom Check-list (SCL-90) and the 30-item Barratt Impulsiveness scale (BIS- 11) were administrated. At the end of six months of caloric restriction, the conventional diet therapy and control weight measurement, the patients were divided into two groups: the group I – 40 participants (48%) who lost ≥ 10% of their initial body weight (successful group) and the group II – 44 participants (52%) who lost < 10% of their initial weight (unsuccessful). Results. There were no significant differences between groups in the demographic data (age, education level, employment, marital status), baseline anthropometric measurements, and in the general psychopathology total score. Groups I and II were significantly different in the total BIS-11 score (p < 0.001) and in Factor II (motor impulsivity) (p < 0.05). Conclusion. Even though the successful and unsuccessful diet responded participatnts did not differ in the general psychopathology and symptom dimensions, our results pointed out impulsivity as a discriminative factor between them. The total impulsivity and Factor II (motor impulsivity) as an indicator of binge eating were higher in the unsuccessfully responding overweight/obese women on the conventional diet treatment. A focus on impulsivity in a psychotherapeutic work might leed to better outcomes in the medical nutrition therapy. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. III41030]